1984
DOI: 10.1128/mcb.4.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p53 protein in cell proliferation as studied by microinjection of monoclonal antibodies.

Abstract: Two monoclonal antibodies against the p53 protein, PAb 122 and 200-47, were microinjected into mammalian cells as a probe to determine the role of the p53 protein in cell proliferation. PAb 122 recognizes the p53 proteins of mouse and human cells but not of hamster cells, whereas 200-47 recognizes the p53 proteins of mouse and hamster cells but not of human cells. The ability of these antibodies to inhibit serumstimulated DNA synthesis of cells in culture correlates with their ability to recognize the species-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
2

Year Published

1986
1986
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(86 citation statements)
references
References 27 publications
2
82
0
2
Order By: Relevance
“…Since p53 has been detected at low levels in normal murine and primate cells (1) but elevated in SV4O-infected and -transformed cells, the function of p53 in each of these systems has been the subject of numerous investigations. A putative function of p53 is the regulation of the cell cycle by controlling exit of cells from Go (33). Given the stable association of p53 with SV40-T antigen in the transformed state (321, the hypothesis has been made that the high levels of p53 which result from this association play a n important part in the induction of transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Since p53 has been detected at low levels in normal murine and primate cells (1) but elevated in SV4O-infected and -transformed cells, the function of p53 in each of these systems has been the subject of numerous investigations. A putative function of p53 is the regulation of the cell cycle by controlling exit of cells from Go (33). Given the stable association of p53 with SV40-T antigen in the transformed state (321, the hypothesis has been made that the high levels of p53 which result from this association play a n important part in the induction of transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent protein products are believed to exert negative control on the cell cycle, regulating passage into the S phase of DNA replication (Mercer et al, 1984). Thus an abnormally low level of wild-type p53 results in a deficiency of the regulatory proteins, allowing largely uncontrolled cell division.…”
mentioning
confidence: 99%
“…Normal p53 is found at low levels in virtually all mammalian cells (Rogel et al, 1985) and various studies have shown elevated levels of the mRNA and protein in a wide variety of tumours and tumour cell lines (Linzer & Levine, 1979;De Leo et al, 1979;Crawford et al, 1981;Benchimol et al, 1982;Rotter, 1983;Thomas et al, 1983) including breast cancer (Cattoretti et al, 1988;Thompson et al, 1990). The normal function of p53 is not known, but it is thought to be involved in the GO/GI to S transition in the cell cycle (Mercer et al, 1984;Ganon & Lane, 1987) where regulation of its activity may be through phosphorylation. Evidence suggests that p53 may behave as a negative regulator, that it is essential for normal growth and that its inactivation may be necessary for the development of malignancy (Lane & Benchimol, 1990).…”
mentioning
confidence: 99%